Skal den offentlige sektor være innovativ? - Langergaard, Louise Li (Slagmark - Tidsskrift for idéhistorie, 2018)
The article unfolds a critical analysis and discussion of innovation as a concept of change in the public sector on the basis of the prevalent understandings of innovation found in research literature and political strategies. It is demonstrated that existing concepts of innovation deemphasize the particular public and democratic dimensions of the public sector, and it is argued that this is problematic from a democratic perspective. The article encourages a rethinking of the innovation concept in a way that breaks with the inheritance from economic innovation theory and a formulation of an innovation theory that has political philosophical concepts such as rights, due process and democracy in focus.